The theft of history - Goody, Jack (Cambridge Cambridge University Press, 2006)
In The Theft of History Jack Goody builds on his own previous work to extend further his highly influential critique of what he sees as the pervasive Eurocentric or occidentalist biases of so much western historical writing, and the consequent 'theft' by the West of the achievements of other cultures in the invention of (notably) democracy, capitalism, individualism and love. Goody, one of the world's most distinguished anthropologists, raises questions about theorists, historians and methodology, and proposes a new comparative approach to cross-cultural analysis which allows for more scope in examining history than an East versus West style.